Sistem Pakar Menentukan Maksimal Kalori Harian Berbasis Mobile - Teddy Santya; Cosmas Eko Suharyanto; Pastima Simanjuntak; Alex Alfandianto (Informatika Universitas Siliwangi, 2019)
The study was conducted because of many concerning event happened in purpose of losing weight in improper methods. By the flow of time with technologies developed in this century, Smartphone became one of necessity because of the feature by many applications which helps a lot in our everyday life of humanity. The Researcher conducted this research of mobile-based application expert system which helps people properly losing their weight, this expert system is a supporting utility for taking care of dietary habit based on the amount of calorie limit calculated by this system, and recommends suitable and healthy food for users. This system is built with React Native framework. The calculation in this system is based on information of weight, height, and age provided by users, and all prediction will not be done without the provided information and every calculation is handled by web-based server-side processing which is developed using Laravel Framework. Inference method used by the researcher is Forward Chaining. This expert system will validate user's requirement to start working on losing weight by using Forward Chaining Inference method. Every successfully registered user will be able to view their calculated information by this system which is maximum calorie value, and list of healthy and recommended foods information provided by the expert herself. From the test results, the Expert System can solve the problem of giving a way to run a proper diet program by adjusting the diet with the calories needed.